The Mechanisms of Sepsis Induced Coagulation Dysfunction and Its Treatment - Zhu L; Dong H; Li L; Liu X (Journal of Inflammation Research)
Lei Zhu,1,2 He Dong,1,2 Lin Li,1,2 Xiaojie Liu1,2 1Department of Anesthesiology, The Affiliated Hospital of Qingdao University, Qingdao, Shandong Province, People’s Republic of China; 2Department of Anesthesiology, Shandong Provincial Key Medical and Heath Laboratory of Anesthesia and Brain Function, Affiliated Hospital of Qingdao University, Qingdao, Shandong Province, People’s Republic of ChinaCorrespondence: Xiaojie Liu, Email mmliuxiaojie@qdu.edu.cnAbstract: Sepsis is a critical condition characterized by organ dysfunction due to a dysregulated response to infection that poses significant global health challenges. Coagulation dysfunction is nearly ubiquitous among sepsis patients. Its mechanisms involve platelet activation, coagulation cascade activation, inflammatory reaction imbalances, immune dysregulation, mitochondrial damage, neuroendocrine network disruptions, and endoplasmic reticulum (ER) stress. These factors not only interact but also exacerbate one another, leading to severe organ dysfunction. This review illustrates the mechanisms of sepsis-induced coagulopathy, with a focus on tissue factor activation, endothelial glycocalyx damage, and the release of neutrophil extracellular traps (NETs), all of which are potential targets for therapeutic interventions.Keywords: sepsis, coagulation dysfunction, thrombosis